Analisis peran sistem keuangan desa (Siskeudes) dalam meningkatkan akuntabilitas keuangan desa: Studi kasus Desa Komus II Kabupaten Bolaang Mongondow Utara - Bawansel, Glorya Indriani; Walandouw, Stanley Kho; Sardjono, Olivia Y. M (Yayasan Widyantara Nawasena Raharja, 2025)
Financial accountability at the village level is a crucial element in achieving transparent and effective local governance. To strengthen accountability and efficiency, the Indonesian government—through BPKP and the Ministry of Home Affairs—introduced the Village Financial System (Sistem Keuangan Desa or Siskeudes), a digital tool designed to support village governments in managing public funds more transparently. This study aims to analyze the role of Siskeudes in improving financial accountability in Komus II Village, North Bolaang Mongondow Regency. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving village officials and local stakeholders. The findings reveal that the implementation of Siskeudes significantly enhances transparency, efficiency, and reliability in village financial reporting. The system simplifies the documentation process, accelerates reporting, and minimizes the risk of fund misuse. Nevertheless, several challenges remain, particularly limited technological infrastructure and insufficient human resource capacity. This study highlights the importance of digital transformation in public sector accounting and the need for continuous capacity-building initiatives for village officials. The findings contribute to the growing body of literature on digital financial governance in developing regions and provide practical implications for policymakers aiming to institutionalize accountability through technology-driven systems.